Pengungkapan Diri di Situs Media Sosial Youtube - Ika Brianti Hadi S; Endang Pratiwi Kurniawan; Irwansyah Irwansyah (JURNAL LENSA MUTIARA KOMUNIKASI, 2021)
Social media is a rapidly growing phenomenon, not only a growing phenomenon in Indonesia. This development is certainly accompanied by the enthusiasm of the community and the existence of social media as a place of self-expression which is increasingly popular and easier to utilize. One of the most popular social media is YouTube. Youtube is a platform where users can upload, watch and share videos. This easily accessible social media platform makes its users come from all ages. This phenomenon is an opportunity for YouTube content creators to make self-disclosure or self-use which is often personal. Self-disclosure plays an important role in life and in the daily life of an individual does not escape the activity of self-disclosure. Researchers want to see the extent to which youtube users use social media as a means of self-disclosure. This research was conducted based on previous studies with similar cases.